THE ANALYSIS OF OPTIMAL PORTFOLIO USING MARKOWITZ METHOD (CASE BASED ON LQ45 SEMESTER 1/2019) (The Indonesian Journal of Business Administration, 2019)
Investment in the capital market is now an interesting thing for the Indonesian people. Beside being used for saving, it also provides more potential profit than saving at bank. The condition of The Indonesian capital market has increase, this is reflected by the increasing JCI movement, so that capital market investment provides so sufficient profit for investors. Price movements in the capital market are influenced by the level of market purchasing power, global economic conditions, government policies, and company performance. Those make stock investment has high risk for investors. The knowledge of stocks and risk is something that is important and needs to be owned by investors or potential investors. This makes investors still have concerns about investment and even suffer losses due to a lack of understanding in investing. Through this research, the author analyzes several alternative portfolio choices used in managing stock investments. The stocks used are included in the LQ45 index for the period February-July 2019 which has the largest market capitalization value. The 10 stocks chosen were ASII, TLKM, UNVR, BMRI, GGRM, BBNI, BBCA, ICBP, BBRI, and HMSP. The historical data used is monthly yield-induced data in 5 years from January 2014 to December 2018. In this research, the author used the Markowitz’s optimization theory for method. The combination of portfolio formed consists of one Equally-weighted portfolio, one optimal risky portfolio, and 28 portfolios in the efficient frontier. The optimal portfolio in efficient frontier is the one that produces the highest profit expectations with a lowest risk value, and the highest Sharpe Ratio value to assess the best performance. Based on 30 alternative portfolio combinations, the best choice of portfolio (10) has a maximum Sharpe Ratio of 5.7315 with a composition of shares with composition of HMSP 15.17%, GGRM 18.93%, BBCA 35.74%, ICBP 6.09%, and BBRI 24.07% with expected return 35.03% with 4.89% risk value. So that the Portfolio (10) can be a reference for investors in managing investments, especially in stocks.Keywords:  Stock, Investment, Portfolio, Markowitz.